Peranan Tunku Abdul Rahman Dalam Mengimbangi Tekanan Perang Dingin, 1957–1966 - Ismail, Noorilham; Abdul Rahman, Zulkanain; Mohamed Ariffin, Nur Dayana (Kajian Malaysia, 2026)
This article focuses on the era of Tunku Abdul Rahman’s administration during the Cold War period from 1957 to 1966. The main objective of this article is to analyse the role Tunku played in balancing Cold War pressures in the Federation of Malaya at the domestic and regional levels through the termination of the Emergency and the formation of the Federation of Malaysia, as well as through effective diplomacy. These circumstances relate to the efforts by Tunku as Chief Minister and later Prime Minister to ensure that the Cold War conflict created by the British in Malaya could be resolved. This article employs a qualitative approach based on archival document research, particularly the National Archives of Malaysia in Kuala Lumpur and The National Archive (TNA) in London. Additionally, this study employed sources from the National Archives of Singapore and documents from the John F. Kennedy Presidential Library in Boston, USA, as well as digital sources such as the Foreign Relations of the United States (FRUS) and the Department of State Bulletin. Finally, this article argues that Tunku’s leadership has managed to balance the pressures of the Cold War at the domestic and regional levels through emergency termination, the formation of the Federation of Malaysia, and effective diplomacy.